WEB BASED LEARNING MEDIA BY UTILITATING LMS MOODLE ON GENETICS SUBSTANCE MATTER - RIZQI MAULIDA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Genetics substance sub topic is abstract, so an appropriate media needed to motivate and help students to understand it. The aim of this study is to produce a web-based learning media by utilizing the LMS Moodle on Genetics substance sub topic and describe media feasibility theoretically based on media experts, Genetics experts, and Biology’s teacher validation. Empirically based on media legibility. The results showed that the web-based learning media on Genetics substance sub topic were feasible for use in learning process with a very decent categories based on media format aspect (93.65%); suitability of the material (100%), and legibility (95.7%). Keywords: LMS Moodle, web-based learning, genetic substance